Desenhando a arqueologia amazônica: de caco a espetáculo e o “modesto museozinho” de Tom Wildi - PINHEIRO, Carolyn Santiago (2021)
This study aimed to create a didactic material on heritage teaching, considering that heritage education collaborates with identity formation and identification with heritage. And in addition to generating an identity with the great monuments that bring a memory of the elite, it is necessary to teach about the hereditament of a minority that is still of little value - in this work, specifically the Marajoara indigenous people. Based on this, the present work produced a comic story about Marajoara ceramics as a product, based on the diary of Tom Wildi - Swiss architect and amateur archaeologist who came to Brazil and visited the island of Marajó several times to collect Marajoara objects to be used as didactic material by public and private schools. Tom Wildi's field records, such as photographs, letters, personal notes, were analyzed so that along with the bibliographical survey done on heritage education and comic book history, this didactic material was produced, which was later applied in the classroom. Obtaining a satisfactory result from this application and opening up other possibilities for the use of this material in the classroom.